Acute Aortic Dissection at the Cardiology Clinic to the University National Hospital Hubert Koutoukou Maga of Cotonou (BENIN) - BORI-BATA, Kamal; DOHOU, Serges Hugues; AIKPON, Donald; AGBO, Mayeul; CODJO, LEOPOLD; ABATTI, Carmel; DANGBEGNON, Maurice; SONOU, Arnaud (My University, 2023)
Introduction: We aimed to describe epidemiological, diagnostic, therapeutic aspects of aortic dissection (AD) managed at the CNHU-HKM of Cotonou (Benin). Methods: It was a retrospective study from january 2018 to july 2023. All patients admitted for AD were enrolled. AD was classified as type A and type B according to Stanford. DA risk factors, socio- demographic characteristics and DA characteristics were studied. Results: Of the 2883 patients admitted during the study period, there were 17 cases of AD, representing a frequency of 0.6%. The mean age was 52 ± 9 years, and the sex ratio was 3.25. Uncontrolled hypertension was the predominant risk factor (88.3%). The main manifestations of AD were chest pain (100%) and aortic insufficiency (52.94%). Chest X-rays showed enlargement of the mediastinum in all patients. Echocardiography showed intimal flap in 62.5%. The aortic angiotomodensitometry, identified 12 type A (70.59%) and 5 type B (29.41%) of AD. Surgical or endovascular treatment was performed in 6 (35.29%) patients. Lethality rate was 47.06%. Conclusion: Aortic dissection was frequent at the teaching clinic of cardiology of CNHU-HKM of Cotonou. Surgical or endovascular treatment wasn't often available, and mortality was high. Prevention of this condition must be the rule, and it requires adequate management of hypertension, which is the most common risk factor.
Keywords: aortic dissection; arterial hypertension; cardiovascular surgery; Benin